Human Capital Mismatches along the Career Path - Ljubica Nedelkoska; Frank Neffke (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2010)
Human capital is transferable across occupations, but only to a limited extent because of differences in occupational skill-profiles. Higher skill overlap between occupations renders less of individuals' human capital useless in occupational switches. Current occupational distance measures neglect that differences in skill complexities between occupations yield skill mismatch asymmetric in nature. We propose characterizing occupational switches in terms of human capital shortages and redundancies. This results in superior predictions of individual wages and occupational switches. It also allows identifying career movements up and down an occupational complexity ladder, and assessing the usefulness of accumulated skill-profiles at an individual's current job.
Keywords: J24; J30; J63; 330; skill mismatch; skill transferability; occupational change; human capital; wages; Humankapital; Erwerbsverlauf; Qualifikation; Matching; Lohn; Arbeitsmobilität; Theorie